2007
DOI: 10.1007/s00125-006-0586-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact of elevated serum level of IL-18 for early renal dysfunction in type 2 diabetes: an observational follow-up study

Abstract: Aims/hypothesis The early identification of type 2 diabetic patients at risk of developing microalbuminuria-an independent risk factor for renal and cardiovascular diseasesis important to improve the patients' outcomes. We investigated whether serum levels of IL-18, a proinflammatory cytokine, were a predictor of early renal dysfunction. Materials and methods A total of 249 Japanese type 2 diabetic patients without overt proteinuria were enrolled in an observational follow-up study (median follow-up 7 years), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 22 publications
4
40
2
1
Order By: Relevance
“…Elevated urinary levels of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), a marker of oxidative stress, predict the progression of diabetic nephropathy in patients with T2D [47]. Patients with T1D or T2D and with higher levels of proinflammatory cytokines and chemokines (interleukin 6, interleukin 18, and monocyte chemoattractant protein-1), high-sensitivity Creactive protein (hsCRP, a marker of subclinical inflammation), or adhesion molecules (soluble vascular cellular adhesion molecule-1 and soluble Eselectin) are at higher risk for developing nephropathy and for advancing to more severe kidney disease [48][49][50][51]. In patients with T1D or T2D, elevated levels of tumor necrosis factor-α receptors are also independently associated with increased incidence of impaired kidney function [52,53].…”
Section: New Risk Factors For Diabetic Nephropathymentioning
confidence: 99%
“…Elevated urinary levels of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), a marker of oxidative stress, predict the progression of diabetic nephropathy in patients with T2D [47]. Patients with T1D or T2D and with higher levels of proinflammatory cytokines and chemokines (interleukin 6, interleukin 18, and monocyte chemoattractant protein-1), high-sensitivity Creactive protein (hsCRP, a marker of subclinical inflammation), or adhesion molecules (soluble vascular cellular adhesion molecule-1 and soluble Eselectin) are at higher risk for developing nephropathy and for advancing to more severe kidney disease [48][49][50][51]. In patients with T1D or T2D, elevated levels of tumor necrosis factor-α receptors are also independently associated with increased incidence of impaired kidney function [52,53].…”
Section: New Risk Factors For Diabetic Nephropathymentioning
confidence: 99%
“…Later studies confirmed the independent and significant association between albuminuria and both serum and urinary IL-18 concentration and, moreover, these levels correlated positively with changes in urinary albumin excretion [118] . Finally, high levels of IL-18 have been suggested as a significant predictor of early renal dysfunction in type 2 diabetes [119] .…”
Section: Il-18 Is An Inflammatory Cytokine Recently Involvedmentioning
confidence: 99%
“…Recently, chronic subclinical inflammation has been thought to be involved in the pathogenesis of DN (4,39). In particular, TNF-␣ is cytotoxic to renal cells and able to induce direct renal injury (8).…”
mentioning
confidence: 99%